SUBSTRATE SUPPLY FOR ENERGY PROCESSES IN CHILDREN (Modern education and development, 2025)
The use of substrates as energy sources changes during the first months of a child's life. Since anaerobic glycolysis predominates in newborns, which provides relatively little energy, and energy expenditure per unit of body mass is very high, the newborn utilizes energy reserves accumulated in utero during the first days after birth to sustain vital processes. The presence of these reserves determines the effectiveness of the child's adaptation to extrauterine life.